Testing the effect of galactic feedback on the IGM at z ∼ 6 with metal-line absorbers - Keating, Laura C.; Puchwein, Ewald; Haehnelt, Martin G.; Bird, Simeon; Bolton, James S. (Oxford University Press, 2016)
We present models of low- and high-ionization metal-line absorbers (O i, C ii, C iv and Mg ii) during the end of the reionization epoch, at z ∼ 6. Using four cosmological hydrodynamical simulations with different feedback schemes (including the Illustris and Sherwood simulations) and two different choices of hydro-solver, we investigate how the overall incidence rate and equivalent width distribution of metal-line absorbers varies with the galactic wind prescription. We find that the O i and C ii absorbers are reasonably insensitive to the feedback scheme. All models, however, struggle to reproduce the observations of C iv and Mg ii, which are probing down to lower overdensities than O i and C ii at z ∼ 6, suggesting that the metals in the simulations are not being transported out into the intergalactic medium efficiently enough. The situation is improved but not resolved if we choose a harder (but still reasonable) and/or (locally) increased UV background at z ∼ 6.